Limitations of Women's Genitals According to M. Syahrur (Ijtihad Method Analysis Study) - Iqbal Dwi Syariansyah; Faisar Ananda; Jamil Jamil (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2021)
The formulation of the research problem is What are the limits of female genitalia according to M. Syahrur and How does M. Syahrur use the ijtihad method in determining the boundaries of female genitalia. This research is library research, using a reference source by M. Syahrur entitled al-Kitab wa al-Qur'analQur'an Mu'ashirahMu'ashirah as the primary reference, as well as other books which include the issue of the boundaries of women'swomen's private parts. The results of the study show that the application of M. Syahrur'sSyahrur's limit theory (nazhariatul hudud) in the problem of the boundaries of women'swomen's private parts states that women cannot be naked because they exceed or exceed the minimum limit (al-hadd al-adnaa). The elements that must be covered and constitute genitalia for women are under the minimum limit (al-hadd al-adnaa), namely the lower part (al-juyub as-sufliyah), (al-juyub as-sufliyah) consisting of the genitals, buttocks, armpits, and breasts. The limitations of women'swomen's private parts in social activation in society include the minimum limits (al-hadd al-adnaa) and parts of women'swomen's bodies that must be covered per public perceptions. Women may not exceed the maximum limit (al-hadd al-a'la). Therefore, they cannot hide their face and hands, such as veiling (niqab). The ijtihad method used by M. Syahrur in determining the boundaries of women'swomen's private parts, with his theory Nazhariatul Hudud explains that there is a minimum limit (al-hadd al-adnaa) and a maximum limit (al-hadd al-a'laaal-a'laa). The minimum limit is the lowest provision of the rules prescribed by Allah SWT, while the maximum limit is the highest limit of a rule. Therefore, it is not permissible to do something less than the minimum limit and also not to do anything more than the maximum limit